2003
DOI: 10.1002/jcb.10430
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature‐induced dimerization of the bovine sperm serine protease, BSp66

Abstract: BSp120 and BSp66 are trypsin-like serine proteases from bovine spermatozoa. The former is active in cryopreserved sperm samples while the latter shows proteolytic activity in recently obtained fresh sperm. Both proteases are immunologically related and co-localize in the apical portion of the sperm head. In Western blots with specific antibodies, sperm samples incubated with reducing agents showed a decrease in the amount of BSp120, while BSp66 was detected with both anti-BSp120 and anti-BSp66 antibodies. BSp1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…BSp66 is a trypsin-like serine protease located at the sperm head of bovine spermatozoa which showed no-crossreactivity with anti-acrosin/pro-acrosin antibodies (Cesari et al 2004a,b). BSp66 dimmerizes by disulfide bonds into a higher form named BSp120 (120 kDa) when bovine spermatozoa is cryopreseved (Cesari et al 2003). As reported for the widespread acrosin system, BSp66 is supposed to be present in other mammalian spermatozoa.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…BSp66 is a trypsin-like serine protease located at the sperm head of bovine spermatozoa which showed no-crossreactivity with anti-acrosin/pro-acrosin antibodies (Cesari et al 2004a,b). BSp66 dimmerizes by disulfide bonds into a higher form named BSp120 (120 kDa) when bovine spermatozoa is cryopreseved (Cesari et al 2003). As reported for the widespread acrosin system, BSp66 is supposed to be present in other mammalian spermatozoa.…”
Section: Introductionmentioning
confidence: 82%
“…This BSp66 is conserved in molecular mass and location at the acrosomal region of hamster spermatozoa. In our previous work, two forms were identified as a monomer and a dimer of a unique protein that formed disulfide bonds after membrane modification induced by cryopreservation or cold storage (Cesari et al 2003). We reported that the dimeric form, named BSp120 was only found in cryopreserved bovine spermatozoa, while the monomeric form, BSp66, was present in fresh bovine sperm samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2003). We found proteolytic activity in bovine spermatozoa that we named BSp66 for bovine sperm protease of 66 kDa, with a different molecular mass compared with other sperm proteases reported (Cesari et al. , 2003).…”
Section: Introductionmentioning
confidence: 66%
“…It dimerises when cryopreserved and forms BSp120 (Cesari et al, 2003). There are evidences of aspartate aminotransferase (AAT), hyaluronidase aminotransferase (HAT) and lactic dehydrogenase (Bhosrekar et al, 1994) in spermatozoa of bovine and GOT GTP, AKP, ACP and LDH in buffaloes (Dhami andKodagali, 1990 andDhami andSahni, 1994).…”
Section: Ne Usmentioning
confidence: 99%